MUSIK KLASIK MOZART SEBAGAI PILIHAN DALAM MENURUNKAN KECEMASAN PRIMIGRAVIDA MENJELANG INTRANATAL - Waifti Amalia (Media Husada Journal of Midwifery Science, 2023)
Anxiety in pregnancy is one of the problems faced by pregnant women in facing labor, especially for first-time pregnant mothers . One of impacts of the prolonged anxiety of pregnant women are getting the high MMR (Maternal Mortality Rate) and IMR (Infant Mortality Rate). Based on preliminary studies which was held on 2 March 2022, there were 13 primigravida third trimester who expererienced anxiety. The purpose of this study is to determine the effect of classical Mozart music therapy on anxiety level of third trimester primigravida in facing labor in Polindes Indah, Amd. Keb Singosari Sub District Malang Regency. The method used is the One Group Pretest-posttest design. The sample used was a 15 third trimester primigravida who met the inclusion criteria during May to July 2013 peeriod. Sampling technique used is Consecutive Sampling. Analysis of these results using Paired T-test analysis of the Test. The analysis shows that of the 15 respondents as given classical Mozart music therapy, all respondents indicate decreased anxiety levels. From the test results obtained Paired T-Test p <0.001, which means there is a significant influence anxiety levels before and after the classic Mozart music therapy. The results of this research was the classic Mozart music therapy can have a significant impact on lowering anxiety level of third trimester primigravida in facing labor in Polindes Indah, Amd. Keb Singosari Sub District Malang Regency